Maabella gen. nov. (Streblidae: Ascodipterinae) from Guangxi Province, China and Vietnam with notes on preservation of Ascodipterinae - Hastriter, Michael W.; Bush, Sarah E. (Zootaxa, 2006)
Endoparasitic Ascodipterinae (Streblidae) were collected from bats from southeast China and northern Vietnam. Among this material, the new genus and species Maabella stomalata is described. The dealate females of this new taxon from China were attached over the joints of the wings of Rhinolophus affinis Horsfield and Rhinolophus macrotis Blyth. They were also removed from the wings of Rhinolophus paradoxalophus (Bourret) and R. macrotis from Vietnam. Clarification of the relationships of the streblid genera Ascodipteron Adensamer, 1896, Maabella, and Paraascodipteron Advani and Vazirani, 1981 is discussed. Techniques are presented for the preparation and preservation of these small obligate parasites.Key words: Ascodipteron, bat flies, endoparasite, neosome, Paraascodipteron, Rhinolophus